Optimizing regenerative braking on electric vehicles using a model-based algorithm in the antilock braking system - Budijono, Agung Prijo; Sutantra, I Nyoman; Pramono, Agus Sigit (Institute of Advanced Engineering and Science, 2023)
The regenerative braking effectiveness of electric vehicles (EVs), with 8-25% range, requires designers to produce better braking systems. The antilock braking system (ABS) was chosen because it offers various advantages, such as enhanced safety considerations, vehicle maneuverability, and so on. The measurement findings revealed that ABS took longer to stop the wheels with the same wheel rotation speed. Because of the lesser differentiation of magnetic flux to time, it created lower induced emf in the generator. ABS 50 Hz performance was 19.5% at 4500 pm, whereas hydraulic brake performance was 21% at the same speed. ABS used model-based algorithms (MBAs) to boost the friction frequency with the wheels from 10 to 50 Hz. As the frequency increased, the ABS graph approached the hydraulic graph, and the ABS performance improved. Although ABS loses to hydraulics in stopping wheel rotation, it gains in saved energy and battery temperature. Longer wheel stop-times allow the rotational kinetic energy of the wheel more time to be converted into electricity.